Efficient Formaldehyde Gas Sensing Performance via Promotion of Oxygen Vacancy on In-Doped LaFeO3 Nanofibers - Lei Zhu; Jiaxin Zhang; Jianan Wang; Jianwei Liu; Wei Zhao; Wei Yan (Nanomaterials)
Perovskite oxide LaFeO3(LFO) emerges as a potential candidate for formaldehyde (HCHO) detection due to its exceptional electrical conductivity and abundant active metal sites. However, the sensitivity of the LFO sensor needs to be further enhanced. Herein, a series of LaxIn1-xFeO3 (x = 1.0, 0.9, 0.8, and 0.7) nanofibers (LxIn1-xFO NFs) with different ratios of La/In were obtained via the electrospinning method followed by a calcination process. Among all these LxIn1-xFO NFs sensors, the sensor based on the L0.8In0.2FO NFs possessed the maximum response value of 18.8 to 100 ppm HCHO at the operating temperature of 180 °C, which was 4.47 times higher than that based on pristine LFO NFs (4.2). Furthermore, the L0.8In0.2FO NFs sensor also exhibited a rapid response/recovery time (2 s/22 s), exceptional repeatability, and long-term stability. This excellent gas sensing performance of the L0.8In0.2FO NFs can be attributed to the large number of oxygen vacancies induced by the replacement of the A-site La3+ by In3+, the large specific surface area, and the porous structure. This research presents an approach to enhance the HCHO gas sensing capabilities by adjusting the introduced oxygen vacancies through the doping of A-sites in perovskite oxides.